2018
DOI: 10.1038/s41467-017-02271-z
|View full text |Cite
|
Sign up to set email alerts
|

Freshwater lake to salt-water sea causing widespread hydrate dissociation in the Black Sea

Abstract: Gas hydrates, a solid established by water and gas molecules, are widespread along the continental margins of the world. Their dynamics have mainly been regarded through the lens of temperature-pressure conditions. A fluctuation in one of these parameters may cause destabilization of gas hydrate-bearing sediments below the seafloor with implications in ocean acidification and eventually in global warming. Here we show throughout an example of the Black Sea, the world’s most isolated sea, evidence that extensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(67 citation statements)
references
References 59 publications
4
62
0
Order By: Relevance
“…For the seismic profile HR31a, the range of variation is narrower (17.5–21.5 °C/km) with an occurrence peak at 20.5 °C/km. These inversion results indicate that a geothermal gradient value of ~20 °C/km could enable a better fit with the current depth of the observed BSR compared to the one of 24.5 ± 0.2 °C/km used for the modeling and derived from in situ measurements (Riboulot et al, ). However, a geothermal gradient of 20 °C/km would make the observed BSR above the predicted steady state BGHS in numerous locations on both seismic profiles.…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…For the seismic profile HR31a, the range of variation is narrower (17.5–21.5 °C/km) with an occurrence peak at 20.5 °C/km. These inversion results indicate that a geothermal gradient value of ~20 °C/km could enable a better fit with the current depth of the observed BSR compared to the one of 24.5 ± 0.2 °C/km used for the modeling and derived from in situ measurements (Riboulot et al, ). However, a geothermal gradient of 20 °C/km would make the observed BSR above the predicted steady state BGHS in numerous locations on both seismic profiles.…”
Section: Discussionmentioning
confidence: 76%
“…During the GHASS cruise, in situ measurements and cores were collected. Geochemical measurements performed on gas hydrate samples, which were collected for the first time in the Romanian sector of the Black Sea, confirmed that the gas entrapped is biogenic methane with a concentration of 99.6% (Riboulot et al, ), and the remaining 0.4% is mainly N 2 . Pore water analyses performed on eight cores revealed a gradual fall in salinity from 22 psu at the seafloor level to near 2 psu at around 25 mbsf.…”
Section: Methodsmentioning
confidence: 91%
See 3 more Smart Citations